The main sources of migrational law - Bozhkarauly, A. (KSU publ., 2016)
This work is devoted to determining the source of the migration law. This paper analyzes the sources in the field of immigration legislation in the Republic of Kazakhstan and the main international documents. In the international acts are considered the main provisions relating to the protection of migrants' rights. Also defines the role of other sources, such as case law, legal practice and judicial decisions of the International Court of UN in the migration law.
Keywords: Immigration Law; regulations; sources of immigration law; legal practice; legal precedent; the UN Convention on the Reduction of Statelessness; migration policy; international regulations